2018
DOI: 10.1111/1753-6405.12803
|View full text |Cite
|
Sign up to set email alerts
|

Transport behaviours among older teenagers from semi‐rural New Zealand

Abstract: The transport decisions made by teenagers, in aggregate, have implications for policy and infrastructure, and findings provide a foundation for discussions around potential changes to driver education programming, the school uniform policy in New Zealand and further research. Implications for public health: Inquiring about everyday transport habits, outside of the trip to school, and activities accessed provided data about an under-researched group, supporting the ecological approach to transport in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Likewise, Watson et al [ 49 ] and Stanley et al [ 50 ] reported that recommended physical activity for school-aged children was not being met, especially for girls, where restrictive school uniform limited physical activity and created an explicit barrier to lunchtime play. Further, in an age of active transport policy, Hopkins et al [ 51 ] found that school uniform style and lack of warmth was a barrier to cycling to school for some female secondary students, and Ward et al [ 52 ] found both garment design and schools’ uniform policy hampered active transport among older teenagers. There are strong indications that uniform garments and policy about which garments can be worn directly impact on students’ physical health outcomes, for female students in particular.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Watson et al [ 49 ] and Stanley et al [ 50 ] reported that recommended physical activity for school-aged children was not being met, especially for girls, where restrictive school uniform limited physical activity and created an explicit barrier to lunchtime play. Further, in an age of active transport policy, Hopkins et al [ 51 ] found that school uniform style and lack of warmth was a barrier to cycling to school for some female secondary students, and Ward et al [ 52 ] found both garment design and schools’ uniform policy hampered active transport among older teenagers. There are strong indications that uniform garments and policy about which garments can be worn directly impact on students’ physical health outcomes, for female students in particular.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on active commuting among adolescents aged 16–19 years are sparse [ 30 , 31 , 32 ]. Also, differences in infrastructure, climate and seasonal variations as well as socioeconomic factors influence active commuting worldwide, making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Active Transportation Provides an Opportunity for Girls to Connect Nature With PA Many reviewed studies emphasized active transportation as a common form of PA that connects adolescent girls to nature. Studies indicated walking and biking as the primary forms of active transportation for girls (Boone-Heinonen et al, 2010;Chillón et al, 2013;Janha et al, 2020;Nelson et al, 2008;Ramírez-Vélez et al, 2017;Thomas, 2015;Ward et al, 2018). One study found that cycling as a form of active transport helped girls incorporate natural environments into their daily routines (Thomas, 2015).…”
Section: Themes Identifiedmentioning
confidence: 99%
“…Further, studies found that active transportation also resulted in girls feeling more connected to nature, as they could reflect and reconnect with their surroundings and themselves (Janha et al, 2020;Thomas, 2015). Several studies noted that girls associate active transportation with well-being, as they can socialize in natural environments while engaging in PA (Dunton et al, 2010;Kudlacek et al, 2020;Ries et al, 2008;Ward et al, 2018). Additionally, researchers found that having peer support while using active transportation encouraged girls to spend more time in natural environments and facilitated more time for PA (Chillón et al, 2013;Dunton et al, 2010).…”
Section: Themes Identifiedmentioning
confidence: 99%
See 1 more Smart Citation